2018
DOI: 10.5194/tc-12-169-2018
|View full text |Cite
|
Sign up to set email alerts
|

On the similarity and apparent cycles of isotopic variations in East Antarctic snow pits

Abstract: Abstract. Stable isotope ratios δ 18 O and δD in polar ice provide a wealth of information about past climate evolution. Snow-pit studies allow us to relate observed weather and climate conditions to the measured isotope variations in the snow. They therefore offer the possibility to test our understanding of how isotope signals are formed and stored in firn and ice. As δ 18 O and δD in the snowfall are strongly correlated to air temperature, isotopes in the near-surface snow are thought to record the seasonal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 63 publications
4
77
0
Order By: Relevance
“…High‐resolution mapping of the spatial variability of stable isotopes and statistical comparisons of the temporal variability recorded by the ice wedges and the driving climate signal, similar to studies performed for ice cores, should provide insight into the signal formation and preservation. Both questions could be supported by numerically modeling signal formation . Very low d values may indicate that the original climate signal has been overprinted due to disequilibrium fractionation, limiting the paleoclimatic significance.…”
Section: Research Topics—state Of the Art And Future Research Prioritiesmentioning
confidence: 97%
“…High‐resolution mapping of the spatial variability of stable isotopes and statistical comparisons of the temporal variability recorded by the ice wedges and the driving climate signal, similar to studies performed for ice cores, should provide insight into the signal formation and preservation. Both questions could be supported by numerically modeling signal formation . Very low d values may indicate that the original climate signal has been overprinted due to disequilibrium fractionation, limiting the paleoclimatic significance.…”
Section: Research Topics—state Of the Art And Future Research Prioritiesmentioning
confidence: 97%
“…It was suggested that the observed low temporal δ/ T may reflect a strong gradient between condensation and surface temperature in winter (Ekaykin et al, ; Landais, Ekaykin, et al, ) and/or the vanishing inversion layer in summer (Landais et al, ). In the central Antarctic Plateau with very low snow accumulation rates (0.016–0.038 m/w.e.a; Ekaykin et al, ; Hou et al, ; Jouzel et al, ; Masson et al, ; Watanabe et al, ), postdepositional processes could significantly modify the isotopic composition of surface snow (Casado et al, ; Laepple et al, ; Münch et al, ; Ritter et al, ). Recent observations in the summer have revealed that the isotopic composition of surface snow in the absence of precipitation varies with changes of the surface vapor isotopic composition (Casado et al, , ; Ritter et al, ; Steen‐Larsen, Masson‐Delmotte, et al, ; Touzeau et al, ), suggesting possible isotopic exchange between surface snow and atmospheric water vapor in the polar regions.…”
Section: Introductionmentioning
confidence: 99%
“…Most individual records have a data resolution ranging from 0.025 to 5 years. In order to limit the influence of nonclimatic noise induced by postdepositional processes (e.g., Münch et al, 2017;Jones et al, 2017;Laepple et al, 2018), they were all 5-year averaged for reconstructing the last 2 centuries and 10-year averaged for reconstructing the last 2 millennia. This lower temporal resolution also limits the potential influence of small age uncertainties.…”
Section: Water Stable Isotope Recordsmentioning
confidence: 99%
“…Using such a controlled framework allows us to precisely assess the performance of the different reconstruction methods via a series of diagnostics including the root mean square error (RMSE) and the correlation coefficients between the reconstructions and the model target (model simulations from which the pseudoproxies are derived), the coefficient of efficiency (CE) of the reconstructions, and the standard deviation of the model truth and the reconstructions. The CE (Lorenz, 1956), which is classically used to measure the skill of reconstructions (e.g., Steiger et al, 2014;Klein and Goosse, 2018), is defined for a time series including n samples as follows:…”
Section: Pseudoproxy Experimentsmentioning
confidence: 99%